The segetal flora of Cynara cardunculus L. (globe artichoke) fields in Sardinia - Vanessa Lozano (Italian Botanist, 2025)
The aim of the present study was to produce a first inventory of the segetal flora in Cynara cardunculus L. (globe artichoke) cropping systems in Sardinia (Italy), to address the limited research available to date, despite the economic significance of this crop. Field surveys were conducted during 2019–2021, at least three times per year, to assess the segetal flora and its main specific features (e.g., life forms, chorology and invasive status in Sardinia), using randomly located georeferenced plots (1 × 1 m) within each field. Based on floristic surveys, it was possible to make an inventory of 113 taxa classified into 91 native species of the Italian flora, 1 archaeophyte, 5 cryptogenic and 16 neophytes, of which 11 were invasive in Sardinia, four naturalized and one casual. Among identified species, 83 were therophytes, 23 hemicryptophytes, 6 geophytes, and 1 chamaephyte. The chorological spectrum shows up the dominance of Mediterranean with 52 species. Widely distributed taxa are represented by 20 species, followed by Eurasian ones with 9 taxa. The most frequent and abundant species were the three native Calendula arvensis (Vaill.) L., Convolvulus arvensis L., and Lolium rigidum Gaudin, the archaeophyte Avena fatua L. s.l., and the two neophytes Oxalis pes-caprae L., and Veronica persica Poir.